FEATURES OF MODERN ENTERPRISE DEVELOPMENT STRATEGIES - Grechan, Alla; Grechan, Pavlo (SWorldJournal, 2025)
This article explores the features of modern enterprise development strategies, taking into account the transformational processes occurring in Ukraine under martial law, hybrid threats, economic digitalization, and the strategic course towards European i